Model Development for Decision Making in Vegetables Distribution in Kabupaten Malang - Oktiarso, Teguh (SPECTA Journal of Technology, 2018)
Food supply chain especially vegetables supply chain must consider the speed of the deliveries due to freshness of the product. Reduced of the freshness of the vegetables faces the great risk of great loss for the farmer and the greengroceries. This paper aimed to develop model for multi criteria decision making based on time to solve vegetables distribution problems from farmers to greengroceries in Kabupaten Malang. Model for decision support system is aimed to determine the minimize delivery time for main vegetables in Kabupaten Malang. There are three variables on three echelons which effects on delivery time before the vegetables decay and worthless. A model for decision support system using real data from 8 sub districts in Kabupaten Malang are obtained to describe the optimal result for several situations in vegetables distribution in Kabupaten Malang to support the decision for distributing the vegetables from farmers to greengroceries with lower cost.